Clinicians' views of factors of importance for improving the rate of VBAC (vaginal birth after caesarean section): a study from countries with low VBAC rates. Issue 1 (December 2016) - Lundgren, Ingela; Healy, Patricia; Carroll, Margaret; Begley, Cecily; Matterne, Andrea; Gross, Mechthild; Grylka-Baeschlin, Susanne; Nicoletti, Jane; Morano, Sandra; Nilsson, Christina; Lalor, Joan
Abstract Background Caesarean section (CS) rates are increasing worldwide and the most common reason is repeat CS following previous CS. For most women a vaginal birth after a previous CS (VBAC) is a safe option. However, the rate of VBAC differs in an international perspective. Obtaining deeper knowledge of clinicians' views on VBAC can help in understanding the factors of importance for increasing VBAC rates. Focus group interviews with clinicians and women in three countries with high VBAC rates (Finland, Sweden and the Netherlands) and three countries with low VBAC rates (Ireland, Italy and Germany) are part of "OptiBIRTH", an ongoing research project. The study reported here aims to explore the views of clinicians from countries with low VBAC rates on factors of importance for improving VBAC rates. Methods Focus group interviews were held in Ireland, Italy and Germany. In total 71 clinicians participated in nine focus group interviews. Five central questions about VBAC were used and interviews were analysed using content analysis. The analysis was performed in each country in the native language and then translated into English. All data were then analysed together and final categories were validated in each country. Results The findings are presented in four main categories with several sub-categories: 1) "prameters for VBAC", including the importance of the obstetric history, present obstetric factors, a positive attitude among those who are centrally involved, early follow-up after CS and antenatal classes; 2) "organisational support and resources for women undergoing a VBAC", meaning a successful VBAC requires clinical expertise and resources during labour; 3) "fear as a key inhibitor of successful VBAC", including understanding women's fear of childbirth, clinicians' fear of VBAC and the ways that clinicians' fear can be transferred to women; and 4) "shared decision making – rapport, knowledge and confidence", meaning ensuring consistent, realistic and unbiased information and developing trust within the clinician–woman relationship. Conclusions The findings indicate that increasing the VBAC rate depends on organisational factors, the care offered during pregnancy and childbirth, the decision-making process and the strategies employed to reduce fear in all involved.